The gift - Jensen, Louise (Grand Central Publishing, 2020)
Jenna is given another shot at life when she receives a donor heart from a girl called Callie. Eternally grateful to Callie and her family, Jenna gets closer to them, but she soon discovers that Callie's perfect family is hiding some very dark secrets....